Toxicity, Positionality, and Ways Forward - F. Todd Goodson (Educational Considerations, 2025)
Currently, our work in education is challenging in ways few anticipated. In such complex and contentious times, it is important to take stock of the situation as dispassionately as possible, take a step back, and breathe. We need to recognize the sincerely held beliefs and altruistic goals of the vast majority of actors seeking to drive change. There are pathways forward, if we sincerely seek common ground.
Keywords: Editorial; Public Discourse